2017
DOI: 10.1182/blood-2016-08-686659
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic approaches for the prevention and treatment of chronic GVHD

Abstract: Clinical outcomes for patients undergoing allogeneic hematopoietic stem cell transplantation continue to improve, but chronic graft-versus-host disease (GVHD) remains a common toxicity and major cause of nonrelapse morbidity and mortality. Treatment of chronic GVHD has previously relied primarily on corticosteroids and other broadly immune suppressive agents. However, conventional immune suppressive agents have limited clinical efficacy in chronic GVHD, and prolonged immune suppressive treatments result in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 98 publications
2
84
0
Order By: Relevance
“…2 These findings are consistent with the central role of autoreactive B cells for cGVHD maintenance, forming the basis for phase 3 testing that is currently underway.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…2 These findings are consistent with the central role of autoreactive B cells for cGVHD maintenance, forming the basis for phase 3 testing that is currently underway.…”
supporting
confidence: 72%
“…In this review series, leading authors in the field present and discuss novel findings in basic T-and B-cell biology research that have led to novel therapeutic targets in cGVHD, 1 mechanistic approaches for prevention and treatment of cGVHD, 2 and a summary of the National Institutes of Health (NIH) Consensus Development Projects on Criteria for Clinical Trials in cGVHD; they then put these concepts into the clinical context. 3 The articles in this review series, "Chronic graft-versus-host disease," include the following:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with B‐cell signalling, inhibiting IKT on T cells is less effective. Previous research showed that blocking IKT leads to CD8 + T cell‐mediated GVL effects, but extensive inhibition of T‐cell activation prevents both GVHD and GVL effects (Cutler et al , ). A phase 2 study with ibrutinib in steroid refractory cGVHD has reported encouraging results, with a 67% overall response rate and a 71% sustained response rate >20 weeks using a daily dose of 420 mg. After a 13.9‐month follow‐up, 75% of responders had corticosteroid doses <0.15 mg/kg/day, and the median patient‐assessed overall cGVHD score decreased, from 7 ( n = 42) to 4 ( n = 14), at week 49.…”
Section: Aberrant B Cell Pathwaysmentioning
confidence: 99%